2013
DOI: 10.3109/14767058.2013.799648
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNPs in genes involved in folate metabolism with the risk of congenital heart disease

Abstract: The CT genotype of NFE2L2-ins1 + C11108T and the TT genotype of GST01-C428T are susceptible factors for CHD. The AG, GG and (AG + GG) genotypes of DHFR-c594 + 59del19 are protective genotypes for CHD. Compound mutants for (MTHFD-G1958A, MTHFR-C677T and MTR-A2756G) and (MTHFD-G1958A, RFC1-G80A and MTR-A2756G) may increase the risk of CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 71 publications
1
40
1
Order By: Relevance
“…This makes 5-formyl tetrahydrofolate cofactor transport 2-fold lower than the wildtype, because the arginine (CGG) at residue 27 could be critical for targeting and integrating protein to the plasma membrane. Many studies showed that women carrying the GA and AA genotypes had higher RBC folate concentrations relative to women carrying the RFC1-80GG genotype, and this was an independent risk factor for their children with CHD [16]. However, our results did not support the above conclusion.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This makes 5-formyl tetrahydrofolate cofactor transport 2-fold lower than the wildtype, because the arginine (CGG) at residue 27 could be critical for targeting and integrating protein to the plasma membrane. Many studies showed that women carrying the GA and AA genotypes had higher RBC folate concentrations relative to women carrying the RFC1-80GG genotype, and this was an independent risk factor for their children with CHD [16]. However, our results did not support the above conclusion.…”
Section: Discussioncontrasting
confidence: 99%
“…We modified SNaPShot protocol [16] and confirmed it using Sanger sequencing established in our laboratory. The primers (with patents) were synthesized by the Genearray Company in China.…”
Section: Genotyping Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a major cause of childhood morbidity and mortality worldwide (Hoffman and Kaplan, 2002;Marelli et al, 2007;Gong et al, 2012;Mamasoula et al, 2013;Wang et al, 2013;Wang et al, 2014;Zhang et al, 2014). It is generally accepted that genetic factors are considered to play important influences on the treatment effectiveness of CHD and the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact etiology of CHD still remains poorly understood. Recently, several studies have indicated that the methylenetetrahydrofolate reductase (MTHFR) gene is an important candidate gene for influencing the prognosis of patients and the risk of CHD (Chambers et al, 2000;Junker et al, 2001;Klerk et al, 2002;Lee et al, 2005;Pereira et al, 2005;Hobbs et al, 2006;Zhu et al, 2006;van Beynum et al, 2007;Brandalize et al, 2009;Garcia-Fragoso et al, 2010;Nie et al, 2011;Gong et al, 2012;Sanchez-Urbina et al, 2012;Yin et al, 2012;Balderrabano-Saucedo et al, 2013;Mamasoula et al, 2013;Mehlig et al, 2013;Wang et al, 2013;Zidan et al, 2013;Wang et al, 2014;Zhang et al, 2014). MTHFR genetic variants, such as C677T and A1298C, have been reported and identified with respect to their genetic influences on the risk of CHD in different populations (Chambers et al, 2000;Junker et al, 2001;Klerk et al, 2002;Nie et al, 2011;Wang et al, 2013;Zidan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%